PENDEKATAN ARSITEKTUR SIMBIOSIS TERHADAP SENTRA HASIL PERIKANAN DI DESA SUNGAI KAKAP, KALIMANTAN BARAT - Vivianty, Monica; Sutisna, Sutarki (Jurusan Arsitektur dan Perencanaan, 2025)
Sungai Kakap Village is a village located on the banks of the Kakap River and directly adjacent to the Natuna Sea, making Sungai Kakap Village famous for its tourism, especially in terms of seafood cuisine and natural scenery for the people of Pontianak City. The issue of seafood restaurants located in the Sungai Kakap Village pier area does not reprocess food waste (especially fish) by throwing it directly into the river. The auction place and fish market also produce waste from leftover fish pieces which then end up in the river. The river water smells bad due to the decomposition of fish protein. The aim of the project is to design an integration so that the Sungai Kakap Village pier area fulfills its potential to rise. The design method applied is